Cognitive late effects following allogeneic stem cell transplantation in haematological cancer patients. (28th March 2021) - Hutchinson, Amanda D.; Thompson, Elise; Loft, Nicole; Lewis, Ian; Wilson, Carlene; Yong, Agnes S. M.
Abstract: Objective: The objective of this exploratory study was to determine the presence and correlates of self‐reported cognition in a sample of haematological cancer patients who had undergone allogeneic stem cell transplantation (SCT). Methods: Haematological cancer patients ( n  = 30) who had undergone allogeneic SCT between one and five years previously and age‐matched control participants ( n  = 30) completed questionnaires assessing cognition, affect, sleep quality and fatigue and an assessment of premorbid IQ. Results: Patients reported significantly poorer perceived cognitive ability ( d  = 1.12) and greater perceived cognitive impairment ( d  = 0.96) than controls. Lower fatigue was significantly associated with greater perceived cognitive ability ( r  = 0.75 patients and controls) and less perceived cognitive impairment ( r  = 0.80 patients; r  = 0.57 controls). Interestingly, depression was significantly correlated with perceived cognitive ability in the control group only ( r  = 0.80). Hierarchical multiple regressions showed that fatigue was a significant predictor of perceived cognitive ability in patients, accounting for 56% of the variance. Conclusions: This study established that self‐reported cognitive ability and cognitive impairment was significantly poorer in haematological cancer patients than controls. Furthermore, fatigue was significantly associated with perceived cognitive ability in patients. Future research should focus on identifying interventions that target fatigue in allogeneic SCT recipients in order to improve quality of life throughout survivorship.